Counting Class: Assessing Social Class Identity Using Quantitative Measures. Issue 162 (13th June 2018) - Soria, Krista M.
Abstract: This chapter analyzes the various ways social class identity has been measured among undergraduate students. Implications of social class definitions and measurement for student affairs practitioners also are discussed.